Wounds of the great venous trunks of the limbs: Importance of its repair in emergency surgery - Goller, Wolfgang G; Torterolo, Edgardo; Luksemburg, Jaime; Castiglioni, Juan C; Cardeza, Héctor; Saccone, Rodolfo; Boschi, Jorge (Cirugía del Uruguay, 1974)
Reconstructive surgery of acute arterial m¡uries had been carried out with succes for the past 15 years. With venous injuries however, ligation rather than repair of the. veins continues. Ligation favorises massive distal venous thrombosis This venous thrombosis is much more responsable of complications, like acute obstruction of a concomitant repaired artery or an artery, which suffered minimal lesions, which by themselves would not have determined no failure, than simple hgation. Vascular injuries need an aggressive approach to repair both vessels. lf only there is carried out the arterial repair, with ligation of the corresponding vein, the defered venous repair must be made, specially when extense venous thrombosis is present. On hand of 28 vascular injuries by gunshot of extremities, authors systematize therapetic measures.